Quality of democracy - Greppi, Andrea (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
Many key elements explain the increasing attention paid to democratic assessment surveys. The construction of objective quality indicators is deemed to be the basis for the development of comparative studies and institutional reform projects. This contribution illustrates some of the most prominent experiences in the field, and the major methodological challenges they are dealing with.
Keywords: Quality of democracy; Democratization index; Political systems’ performance; Democratic assessment